Penerapan Data Deret Waktu dalam Peramalan Permintaan Semen Curah Tipe Ezpro Menggunakan Perangkat Lunak POM QM (Studi Kasus di PT. WXY) - Sholihin, Farhan Aufa; Ernawati, Dira (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
PT WXY, which operates in the cement industry, seeks to improve operational efficiency by forecasting demand for EzPro type bulk cement for the coming period. This study aims to determine the most effective forecasting method using two approaches, namely Moving Average and Single Exponential Smoothing, and analyzing historical data for 10 months using POM QM V5 software. The accuracy of the forecasting results is evaluated by Mean Squared Error (MSE). The results show that the Single Exponential Smoothing method has an MSE of 1,113,479,000, lower than the Moving Average method which reaches 1,721,099,000. Therefore, Single Exponential Smoothing is chosen as the best forecasting method to improve accuracy, optimize distribution schedules, and reduce operational risks such as excess or shortage of stock. Consistent application of this method is expected to support the smoothness of the supply chain and improve the company's operational efficiency. Keywords: Demand Forecasting, POM QM V5, Single Exponential Smoothing, Single Moving Average.